Cobalt‐Based Materials in Supercapacitors and Batteries: A Review - Jyothi A. Goudar; Thrinethra S. N.; Sharanappa Chapi; Murugendrappa M. V.; Mohammad Reza Saeb; Mehdi Salami‐Kalajahi (Advanced Energy & Sustainability Research)
Energy demand has become a persistent concern and high‐performance energy storage systems have increasingly undergone development. Supercapacitors and batteries pose great impact on energy storage and garner a great deal of attention from technologies and researchers alike. The performance of energy saving devices is primarily determined by the electrode material in terms of high specific capacitance, excellent conductivity, remarkable natural abundance, and unique electrochemical qualities, also large surface area. Cobalt (Co)‐based materials are unique electrode materials widely used in energy storage devices. Nevertheless, a combination of Co and ferrite materials such as nickel, zinc, and copper, or Co/nonferrite materials like metal–organic frameworks and layered double hydroxides has improved their ultimate efficiency. This review deals with energy storage applications of Co‐based materials, categorizing ferrites, their electrochemical characterization, performance, also design and manufacturing intended to supercapacitors and batteries applications. Summarizing the main outcomes of the literature on batteries and supercapacitors, energy storage systems comprising Co‐based materials combined with carbon nanotubes, graphene, silica, copper, zinc, nickel, cadmium, ferrous, and lanthanum are reviewed and discussed. Lithium‐ion batteries are investigated specifically, and perspectives on Co‐based ferrite development for future generations of supercapacitors and batteries are outlined.